in Probability edited by
8,241 views
47 votes
47 votes

Consider the following experiment.

Step 1. Flip a fair coin twice.

Step 2. If the outcomes are (TAILS, HEADS) then output $Y$ and stop.

Step 3. If the outcomes are either (HEADS, HEADS) or (HEADS, TAILS), then output $N$ and stop.

Step 4. If the outcomes are (TAILS, TAILS), then go to Step $1.$

The probability that the output of the experiment is $Y$ is (up to two decimal places)

in Probability edited by
8.2k views

3 Comments

A much easier way for this would be:

Let $W = \text{We get a Y}$.
Let $D = \text{The game is decided after the first two tosses}$

The crucial observation here is that if we don't finish after the first two tosses, we are facing the same game again.

Therefore, $P(W/D^c) = P(W) \implies P(W/D) = P(W)$.

This gives us that $P(W) = P(W  \cap D)/P(D) = \frac{1/4}{1/4 + 2/4} = 0.33$
13
13
Sample Space = $\{Y,N\}$

Therefore, $P(Y)+P(N)=1$

 

Number of favourable cases for $P(Y)=1$

Number of favourable cases for $P(N)=2$

Total cases = $3$ (NOT 4)

 

So, $P(Y)=1/3=0.33$
8
8
is this a Markov chain?
0
0

4 Answers

51 votes
51 votes
Best answer
Answer is ${0.33}$

$1^{st}$ time it is ${0.25}\left(\dfrac{1}{4}\right),$ when tail tail comes, entire process gets repeated, so next time probability of $Y$ to happen is ${0.25}\times {0.25}\left(\dfrac{1}{4}\times \dfrac{1}{4}\right),$ likewise it goes on as infinite GP

Sum of infinite GP $= \dfrac{a}{(1-r)}$

here, $a= \dfrac{1}{4}$ and $r =\dfrac {1}{4}$

so answer becomes $\dfrac{1}{3}$ i.e ${0.33}$
edited by

4 Comments

@swami_9 Are you really dumb or just acting like one?

3
3

@JAINchiNMay First time it is $1/4$, 2nd time it is $1/4*1/4$ and so on. Sir has just written $0.25 = 1/4$.

That’s why $a= 1/4 \ and  \ r= 1/4$

0
0
ohh my bad thanks
1
1
36 votes
36 votes

Answer should be 0.33

$P(TH)=\dfrac{1}{4}$

$P(HH + HT)=\dfrac{1}{2}$

now if $TT$ comes then toss again,

So, $P(TTTH)=\dfrac{1}{16} $ and so on.... $P(TH+TTTH+\ldots) = \dfrac{1}{4} + \dfrac{1}{16}+\ldots= \dfrac{1}{3}$

edited by
29 votes
29 votes

P(getting the output Y) = P(TH) +P(TTTH) + P(TTTTTH) + P(TTTTTTTH) +  P(TTTTTTTTTH)+  P(TTTTTTTTTTTH)...........

 P(getting the output Y) = 1/4 + 1/42 +1/43 +1/44 +1/45 +1/46+................ = (1/4) / ( 1- 1/4) =1/3

The correct answer is 0.33 .

1 comment

I also applied the same approach... Easy to understand.
1
1
5 votes
5 votes

You can correct me if I am wrong.

1 comment

bro you adding p(TH) case in the first if we get (TH) we simply stop as mentioned in question the how its possible please explain if am wroong

0
0
Answer:

Related questions